A Study of the Enablers of Social Capital in an Organization : A Total Interpretative Structural Modelling and MICMAC Approach - Panackal, Nehajoan; Venkataramani, Bhama (Prabandhan: Indian Journal of Management, 2021)
Purpose : The purpose of this research was to study the enablers of social capital that encouraged knowledge sharing practices among faculty members. We designed a model that showed the relation and linkages between the identified enablers. Design/Methodology : The enablers of social capital were identified systematically through extant literature review. We validated the identified enablers through expert opinion. Once the enablers were finalized, the research techniques : total interpretative structural modelling (TISM) and MICMAC analysis were used to study the nature of interaction between the enablers. Findings : The derived model had four levels of interactions. Shared Beliefs and Reciprocity were identified as the most important enablers. Shared Beliefs and Bonded Solidarity mutually impacted each other and had a role in creating a sense of social cohesion. Reciprocity helped to strengthen the organization culture. Organizational Culture and Bonded Solidarity were placed at Level 2. Generalized Trust and Moral Obligation impacted the levels of Employee Engagement, Closed Structure Networks among faculty members, Intrinsic Motives, and Affective Commitment. Based on the MICMAC analysis, Reciprocity, Organizational Culture, and Bonded Solidarity were the linkage variables, Closed Structure Networks, Generalized Trust, Intrinsic Motives, and Affective Commitment were the drivers. Shared Beliefs was a dependent variable and Moral Obligation and Employee Engagement were the autonomous variables. Originality and Significance of the Study : The paper proposed a framework of the interrelationships of the enablers which had a role in improving social capital. This research would benefit researchers, HR professionals, management involved in the education sector, and faculty members.